Peningkatan Kapasitas Pelaku Usaha Keripik Ubi Jalar dalam Perbaikan Mutu Produk di Desa Lingkar Kampus - . Warcito; Tjahja Muhandri; . Subarna (Institut Pertanian Bogor, 2015)
The objectives of community development activity are: 1) Increase the capacity of sweet potato chips business groups; 2) Improving the quality and diversification of products sweet potato; and 3) Improvement of product packaging sweet potato chips. This activity is applied at Petir Village, Darmaga Subdistrict and Cihideung Ilir Village, Ciampea Subdistrict, Bogor Regency. The methods are problem analysis group activities, training, and mentoring. Based on results of discussion the enchancement of group members capacity do by training. Training can improve the ability of businessmen amounted to 18.6% through pre-test and post-test. Improving the quality do by repairs the production process, especially in the process of slicing and frying. Increased marketing do by improved packaging and gain PIRT license.